Diogenes Laertius and the stoic ethics - Silva de Almeida, José Carlos (2025)
This article presents important concepts of Stoic ethics and their connections found in the version of Diogenes Laetius in book VII of Lives and doctrines of the eminent philosophers. Unlike Cicero in book III of De finibus, Diogenes' formulation is not marked by rhetorical skills and ends up following the technicality present in book II of Eclogues by Arius Didymus. Diogenes, without worrying about giving a more public appearance to Stoic exhibitions, does not hide the difficulties and frequent eccentricities of Stoic philosophy, which sometimes presents unattractive and even tedious reasoning.